2011
DOI: 10.1177/009102601104000202
|View full text |Cite
|
Sign up to set email alerts
|

A Research on the Influence of Leadership Style and Job Characteristics on Job Performance among Accountants of County and City Government in Taiwan

Abstract: The objectives of this paper are to explore the effect of leadership style and job characteristics on job performance and examine the mediating effect of organization commitment on the leadership style, the job characteristics and the job performance as well as to provide the management suggestions according the research findings.The questionnaires are applied to the accountants of county/city government in Taiwan, and the convenience sampling is adopted. The following research findings are described after con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 8 publications
3
47
1
2
Order By: Relevance
“…Other researchers (Liu et al, 2010;Chu and Lai, 2011;Galletta et al, 2011) have also reported that job autonomy is a significant predictor of organizational commitment. With regard to job autonomy and its association with WFPC, this study found that an increase in job autonomy led to an increase in WFPC.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Other researchers (Liu et al, 2010;Chu and Lai, 2011;Galletta et al, 2011) have also reported that job autonomy is a significant predictor of organizational commitment. With regard to job autonomy and its association with WFPC, this study found that an increase in job autonomy led to an increase in WFPC.…”
Section: Discussionmentioning
confidence: 91%
“…This is further supported by results from the study of Galletta et al (2011) concerning the attractive working environment characteristics which showed that job autonomy perceived by workers was among the most important factors related to retention. Other studies also reported that job autonomy had a significant relationship with organizational commitment (Liu et al, 2010;Chu and Lai, 2011). Based on the above argument, the following hypothesis was formulated.…”
Section: Hypothesismentioning
confidence: 94%
“…He defined task performance as " the proficiency with which incumbents perform activities that are formally recognized as part of their jobs; activities that contribute to the organization's technical core either directly by implementing a part of its technological process, or indirectly by providing it with needed materials or services". While Contextual performance means the extra-role behaviors engaged in by employees over and above their task requirements, which emphasizes selflessness and mutual cooperation (Chu, & Lai, 2011). In recent years, the definition of job performance has been expanded to three broad dimensions: task performance, organizational citizenship behavior and counterproductive behaviors.…”
Section: Task Performancementioning
confidence: 99%
“…Piccolo and Colquitt (2006) proposed that jobs regarded as important, challenging and allows employees to use various skills and talents are more likely to create perceived meaningfulness in employees' job, while the meaningfulness of work could improve employees' job performance because they believe that their job can make significant contributions to the society (Ghosh et al, 2015). Similarly, Chu and Lai (2011) founded that skill variety is significantly positively influence the task performance, because task performance is the core dimension of job performance and occupies the greatest weight of it ( Rotundo, & Sackett, 2002). Accordingly, we can image that skill variety facilitate employee's task performance positively.…”
Section: Skill Variety and Task Performancementioning
confidence: 99%
See 1 more Smart Citation